Neural mechanisms of savant calendar calculating in autism: An MEG-study of few single cases - Dubischar-Krivec, A.; Bolte, Sven; Braun, C.; Poustka, F.; Birbaumer, N.; Neumann, N. (Academic Press, 2014)
This study contrasted the neurological correlates of calendar calculating (CC) between those individuals with autism spectrum disorder (ASD) and typically developing individuals. CC is the ability to correctly and quickly state the day of the week of a given date. Using magnetoencephalography (MEG), we presented 126 calendar tasks with dates of the present, past, and future. Event-related magnetic fields (ERF) of 3000. ms duration and brain activation patterns were compared in three savant calendar calculators with ASD (ASDCC) and three typically developing calendar calculators (TYPCC). ASDCC outperformed TYPCC in correct responses, but not in answering speed. Comparing amplitudes of their ERFs, there was a main effect of group between 1000 and 3000. ms, but no further effects of hemisphere or sensor location. We conducted CLARA source analysis across the entire CC period in each individual. Both ASDCC and TYPCC exhibited activation maxima in prefrontal areas including the insulae and the left superior temporal gyrus. This is in accordance with verbal fact retrieval and working memory as well as monitoring and coordination processes. In ASDCC, additional activation sites at the right superior occipital gyrus, the right precuneus, and the right putamen point to visual-spatial strategies and are in line with the preference of autistic individuals for engaging posterior regions relatively more strongly in various reasoning and problem solving tasks. © 2014 Elsevier Inc.